OTONOMI DESA ADAT: SEBUAH FATAMORGANA? KASUS DARI DESA ADAT INTARAN, BALI, INDONESIA - Rahmatunnisa, Mudiyati; Ramaditya, Fauzan; Putra, Haelvyn Pratagrahana; Khairunnisa, Anandya (Universitas Jenderal Ahmad Yani, 2023)
This study examines the empirical experience of indigenous village autonomy in Indonesia as normatively regulated in the 1945 Constitution and the recent 2014 Law on Regional Government. The prolonged debate by many on the issue has mainly focused on how autonomous indigenous villages have actually been due to various forms of state intervention (also referred to as